Standardization of the digital cartography procedure of the thematic geological maps and print preparation - Komac, Marko (Geologija, 2001)
The Geological Survey of Slovenia has approached to the whole print preparation procedure for the first time in year 2000. For the “Guinea pig” of this project the Structural-tectonic Map of Slovenia in scale 1:250.000, which was elaborated by Marijan Poljak, was chosen.